IAMSLI 25th Anniversary Conference, 1999 - James W. Markham (Issues in Science and Technology Librarianship, 1999)
The International Association of Aquatic and Marine Science Libraries and Information Centers (IAMSLIC) held its 25th Anniversary Celebration and Annual Conference October 16-22, 1999, in Woods Hole, MA. The conference included 3 pre-conference workshops, on HTML, Web Design, and Ariel, eight invited keynote speakers, 19 contributed papers, and 11 poster presentations.